Immersed into our clothes. Are wearable technologies a potential gateway to extra-virtual immersion? - Fales, Ludovica (Cinergie – Il Cinema e le altre Arti, 2015)
What would happen if a Tweet appearing on the Twitter dress is re-tweeted and appears the dress of another unknown user in the same room, causing them to recognize each other in person through a message launched in the web? A new wave of interactive ready-to-wear technologies is dealing with the concept of embedding technology into the body in an even more radical way than the much talked about “Apple watches” or “Goggle glasses”. What will this new environment imply? Will this create an entire new conception of immersion which will alter altogether the real/ virtual dichotomy (Jenkins, 2004, 2006, 2009, 2013 )? What elements will come into play within the extra-virtual immersive environment? What will the differences be with other immersive environments like Virtual Reality or Augmented Reality?